Historiography of volunteer activities in Ukraine in times of extreme trials: methodological problems of polydisciplinaryness. - Teluha Yevgenіі (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The purpose of the study. To investigate and analyze the problems of scientific thought and the evolution of the study of the volunteer movement in Ukraine. The research methodology. The research used general scientific methods, the method of historiographical analysis and synthesis, and the main methods of historical research. Scientific novelty. For the first time, the methodological problems of the multidisciplinarity of scientific thought regarding the issue of volunteering in Ukraine were considered in the study. Topicality. Analysis of the latest research and publications using general scientific and specifically historical methods allows us to study such a social phenomenon as volunteering more widely. Conclusions. Scientific work on the study of the volunteer movement in Ukraine, thanks to specialists in various fields of science, contributes to the well-founded implementation of scientific achievements in practical activities and interaction of volunteering with the state. A multidisciplinary approach in research makes it possible to increase the historiographical studies of this issue many times over, which in turn stimulates an in-depth and versatile, further study of the volunteer movement in Ukraine. Also, it is worth noting that the historiography of the issue significantly affects the institutionalization of the volunteer movement, which in turn strengthens the defense capability of our state against the background of Russian expansion. The full-scale armed aggression of the Russian Federation against our country added another historical stage, which, upon its completion, will be the subject of scientific discussions. Therefore, the prospect of further research of the volunteer movement in Ukraine, from the point of view of both the historical aspect and related sciences, will arouse the scientific interest of many researchers.